CONCEPT OF ZAKAT AND ISLAMIC PHILANTHROPY ORGANIZING FOR PALESTINE IN MAQASHID SHARIA PERSPECTIVE - Hakim, Ridwan; Syauqi Beik, Irfan; Ibdalsyah, Ibdalsyah; Renaldi, Haris (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
Zakat is one of the aspects of Islamic economics that has a very important role in equity. As one of the shari'a, zakat has a special discussion regarding maqashid or the purpose of shari'a; both in terms of collection and distribution. The Palestinian issue has long been the target of Islamic philanthropy and even zakat. This qualitative research uses a normative legal method where maqashid sharia is used to examine the law of zakat. The results of the study conclude that the law of collecting zakat and then distributing it to Palestine is permissible and even recommended. Of course, by paying attention to the balance of distribution between the existing emergencies in the country and in Palestine. In raising zakat, amil or philanthropic institutions must pay attention to education aspects of fardhu kifayah in the Palestinian struggle and aspects of the growth of muzakki assets. In distribution in Palestine, it must meet the needs of maintaining the Al-Aqsa mosque and holy places as well as the needs of fulfilling the human rights of the Palestinian people.